PENGARUH COMPETITIVE ADVANTAGE DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA USAHA DAN IMPLIKASINYA PADA KEBERLANJUTAN USAHA - Purwatiningsih Purwatiningsih; Nofryanti Nofryanti; Iin Rosini (Jurnal Ilmiah Global Education, 2023)
This study aims to look at the effect of competitive advantage and environmental uncertainty on business performance and the implications for the sustainability of MSME businesses in Depok City. This type of research is associative quantitative (causality) and the population in this study are MSME business actors in Depok City. The sample of this research was determined by convenience sampling method so that the total sample is 100 samples. The data analysis technique used is Structural Equation Modeling (SEM) using the SmartPLS program data processing. The results showed that there was a significant influence of competitive advantage on business performance in Depok City. There is a significant influence of environmental uncertainty on business performance in Depok City. There is a significant influence of competitive advantage on the sustainability of MSME businesses in Depok City. There is a significant influence of environmental uncertainty on the sustainability of MSME businesses in Depok City. There is a significant influence of business performance on the sustainability of MSME businesses in Depok City. There is a significant influence of competitive advantage on the sustainability of MSME businesses through business performance in Depok City and there is a significant influence from the influence of environmental uncertainty on the sustainability of MSME businesses through business performance in Depok City.